ESR Investigations of the Submicron LiFe1−xMnxPO4 Systems - Tatiana Gavrilova; Adilya Yagfarova; Sergey Khantimerov; Dinar Abdullin; Nina Kosova; Nail Suleimanov (Magnetochemistry, 2022)
Magnetic properties of the submicron carbon-coated LiFe1−xMnxPO4 (x = 0, 0.01, 0.1) systems were investigated using the electron spin resonance (ESR) method. The observed ESR signal consisted of two broad resonance lines with a Lorentzian line shape for all samples. The temperature dependence character of the integral intensity of these lines changed significantly with increasing manganese concentration, indicating a change in the nature of the magnetic interactions between the manganese and iron ions. We suggest that the noticeable capacity loss observed in the LiFe1−xMnxPO4 systems with increasing Mn content can be explained by the random distribution of Mn ions and changes to the type of magnetic ordering in these systems, despite the attractiveness of the electrochemical Mn2+/Mn3+ pair compared with Fe+2/Fe+3.